2022
DOI: 10.1186/s12889-022-13420-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between the 24-hour movement guidelines and executive function among Chinese children

Abstract: Objective Childhood is a critical period for brain development. However, it remains unknown whether the behaviors in a typical 24-h day are related to children’s executive function (EF). This study aimed to investigate the relationship between the 24-h movement guidelines and children’s EF. Method Children aged 7–12 years (n = 376) were studied in 2017 in China. Physical activity (PA) was accelerometer-derived, while screen time (ST) and sleep dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…This can be attributed to the similar proportion of boys and girls meeting the MVPA recommendation ( p = 0.824) in our study. We also found a low prevalence of meeting the MVPA recommendation (13.3%), which is similar to previous studies (Chen et al, 2021; Roman‐Viñas et al, 2016; Zeng et al, 2022). Moreover, the higher prevalence of meeting the ST recommendation in our study is consistent with one previous study conducted in China, which indicated that 82.4% of Chinese children met the ST recommendation (Zeng et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This can be attributed to the similar proportion of boys and girls meeting the MVPA recommendation ( p = 0.824) in our study. We also found a low prevalence of meeting the MVPA recommendation (13.3%), which is similar to previous studies (Chen et al, 2021; Roman‐Viñas et al, 2016; Zeng et al, 2022). Moreover, the higher prevalence of meeting the ST recommendation in our study is consistent with one previous study conducted in China, which indicated that 82.4% of Chinese children met the ST recommendation (Zeng et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…We also found a low prevalence of meeting the MVPA recommendation (13.3%), which is similar to previous studies (Chen et al, 2021; Roman‐Viñas et al, 2016; Zeng et al, 2022). Moreover, the higher prevalence of meeting the ST recommendation in our study is consistent with one previous study conducted in China, which indicated that 82.4% of Chinese children met the ST recommendation (Zeng et al, 2022). The higher prevalence may be attributed to the elevated levels of parental education, as more than 80% of parents held a college/university degree or higher in our study.…”
Section: Discussionsupporting
confidence: 92%
“…While the above study focused on the older population, further logistic regression analysis on adolescents also showed a strong correlation between poorer muscle strength and higher prevalence of executive dysfunction. The study results found a higher risk of cognitive flexibility impairment in the muscle strength index < P 20 group compared to adolescents with muscle strength index > P 80 ( OR = 1.820, 95% CI : 1.111, 2.982) ( P < .05) (Zeng, Cai, et al, 2022). This finding is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 93%
“…Inadequate or impaired executive function development results in learning disabilities, attention deficits, anxiety and depression, and schizophrenia, and this correlation continues into adulthood (Best et al, 2011). Research confirms that muscle strength is an important variable in promoting executive function in adolescents (Zeng, Cai, et al, 2022). Recent studies have found that muscle strength has a positive and significant effect on improving functional brain plasticity, executive function and response inhibition (Arts et al, 2016;Yoon et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Zeng et al (2022) found that meeting more recommendations of the 24‐h movement guidelines was associated with higher EF scores in children aged 7–12 years. Another cross‐sectional study also reported that associations with superior global cognition were found in elementary school students who met recommendations compared with those who met none of the recommendations (Walsh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%